2021
DOI: 10.1177/23992026211027692
|View full text |Cite
|
Sign up to set email alerts
|

Availability and accessibility of monoclonal antibodies in Bosnia and Herzegovina: Findings and implications

Abstract: Background: Monoclonal antibodies (mAbs) represent the most numerous and significant group of biotherapeutics. While mAbs have undoubtedly improved treatment for many chronic diseases, including inflammatory diseases, they are typically expensive for health care systems and patients. Consequently, access to mAbs has been a problem for many patients especially among Central and Eastern European (CEE) countries. However, biosimilars can potentially help with costs, although there are concerns with their effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Defined daily doses (DDDs) were used where possible for utilization to enhance the comparisons between countries, with DDDs recognized as a robust measure for undertaking crosscountry utilization research (Godman et al, 2014Tubic et al, 2021).…”
Section: Cross National Drug Utilization and Expenditure Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Defined daily doses (DDDs) were used where possible for utilization to enhance the comparisons between countries, with DDDs recognized as a robust measure for undertaking crosscountry utilization research (Godman et al, 2014Tubic et al, 2021).…”
Section: Cross National Drug Utilization and Expenditure Studymentioning
confidence: 99%
“…High patient co-payments and reimbursement issues with biologic medicines have resulted in many Central and Eastern European (CEE) countries struggling to fund originator biologic medicines (Baumgart et al, 2019;Tubic et al, 2021). Rencz et al (2015) found only 0.25% of all patients diagnosed with psoriasis were treated with biologics among six researched CEE countries, with a 14.6-fold difference in utilization rates between them (Rencz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This recognises that such discussions are more difficult in some LMICs where patients are struggling to fund even standard insulins within public healthcare systems, with these discussions continuing exacerbated by the recent COVID-19 pandemic (Ogunleye et al, 2020). However, this is not universal as seen with growing use of long-acting insulin analogues, including biosimilars, in a number of Asian and CEE countries (Godman et al, 2021c;Godman et al, 2021d;Tubic et al, 2021).…”
Section: Developments In Insulin Administration and The Implicationsmentioning
confidence: 99%
“…This is welcomed as there have been concerns in CEE countries regarding the availability and funding of biological medicines to treat patients with rheumatoid arthritis, psoriasis, and inflammatory bowel disease (Putrik et al, 2014;Kostic et al, 2017;Baumgart et al, 2019). Among CEE countries, including Bosnia and Herzegovina, the Czech Republic, and Estonia, there has been high use of long-acting insulin analogues versus other forms of insulin, with high expenditure on long-acting insulin analogues also seen in Romania in recent years (Godman et al, 2021d;Tubic et al, 2021), with this trend continuing.…”
Section: Introductionmentioning
confidence: 99%